PERLINDUNGAN HAK ASASI MANUSIA TERSANGKA TINDAK PIDANA TERORISME - Eva Noviyana; Usman; Elizabeth Siregar (Berajah Journal, 2026)
This study aims to examine the provisions for protecting the human rights of terrorism suspects in Law Number 5 of 2018 and to formulate a more balanced criminal law policy to address existing normative weaknesses. The background to this research is based on the widespread allegations of human rights violations during the arrest and detention of terrorism suspects, one example of which was the death of Siyono in 2016. This study uses a normative juridical method by examining primary legal materials in the form of laws and regulations, secondary legal materials in the form of literature and previous research, and tertiary legal materials to complement the analysis. The results indicate that although Article 25 paragraph (7) and Article 28 paragraph (3) of Law Number 5 of 2018 mandate respect for human rights during the arrest and detention process, the provisions on sanctions in Article 25 paragraph (8) and Article 28 paragraph (4) remain vague because they do not specifically specify the type and severity of sanctions. This ambiguity in norms creates legal uncertainty that contradicts the principle of lex certa, the theory of natural rights, and the principle of due process of law. This research concludes that Law Number 5 of 2018 has three structural weaknesses: the lack of firm sanctions for officials who violate human rights, the absence of an independent oversight body, and the lack of guaranteed legal assistance for suspects. Therefore, it is necessary to add new articles containing firm criminal and administrative sanctions, an independent judicial oversight mechanism, and the obligation to provide free legal assistance to terrorism suspects.